2016
DOI: 10.1016/j.jad.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation biomarkers in adolescents with or at high-risk for bipolar disorder

Abstract: Background Prior work suggests that adult bipolar disorder (BD) is associated with increased oxidative stress and inflammation. This exploratory study examined markers of lipid and protein oxidation and inflammation in adolescents with and at varying risk for BD type I (BD-I). Methods Blood was obtained from four groups of adolescents (9–20 years of age): (1) healthy comparison subjects with no personal or family history of psychiatric disorders (n = 13), (2) subjects with no psychiatric diagnosis and at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…In addition, higher protein carbonyl and lipid hydroperoxide content were determined in adults compared to adolescents with BD [101] and the increased levels of an early component of the peroxidation chain in euthymic older patients with BD support the hypothesis of a persistent effect of ROS in patients with BD into late life [102]. It was observed in a recent exploratory study that the plasma levels of oxidative stress markers were lower in adolescents with fully syndromal BD than controls, while levels in the at-risk groups were between healthy controls and fully syndromal BD supporting a role of oxidative stress in BD risk progression [103]. Furthermore, Andreazza and colleagues observed that superoxide dismutase activity was higher in manic and depressed patients compared to euthymic patients and controls [104].…”
Section: Oxidative Stresssupporting
confidence: 52%
“…In addition, higher protein carbonyl and lipid hydroperoxide content were determined in adults compared to adolescents with BD [101] and the increased levels of an early component of the peroxidation chain in euthymic older patients with BD support the hypothesis of a persistent effect of ROS in patients with BD into late life [102]. It was observed in a recent exploratory study that the plasma levels of oxidative stress markers were lower in adolescents with fully syndromal BD than controls, while levels in the at-risk groups were between healthy controls and fully syndromal BD supporting a role of oxidative stress in BD risk progression [103]. Furthermore, Andreazza and colleagues observed that superoxide dismutase activity was higher in manic and depressed patients compared to euthymic patients and controls [104].…”
Section: Oxidative Stresssupporting
confidence: 52%
“…244 A study of adolescents with or at risk for PBD found that adolescents with PBD had significantly lower LPH vs controls, with non-symptomatic adolescents at familial risk falling between the other groups. 245 Finally, a study of 29 adolescents with PBD and 25 HCs found that LPH−BDNF correlations were significantly different between adolescents with PBD and HCs, and that, among adolescents with PBD in the top half of the distribution of BDNF levels, greater LPH levels were associated with poorer executive function. 246 …”
Section: | Peripheral Biomarkersmentioning
confidence: 99%
“…Most recently, plasma levels of lipid peroxidation (lipid hydroperoxide and 4-hydroxy-2-nonenal, 8-isoprostane), protein oxidation (protein carbonyls), and inflammation (interleukin 1, interleukin 6, interleukin 10, interferon gamma, TNF alfa) were assessed in four groups of adolescents (9–20 years of age), consisting of high-risk offspring, ultrahigh-risk offspring, first-episode BD patients, and healthy controls [90]. The levels of lipid hydroperoxide, an early stage lipid peroxidation marker, showed a decreasing trend along the spectrum of risk for BD-I, while there was no difference in the late stage lipid peroxidation markers (4-hydroxy-2-nonenal, 8-isoprostane), protein carbonyls, and inflammatory markers among groups [90].…”
Section: Resultsmentioning
confidence: 99%
“…The levels of lipid hydroperoxide, an early stage lipid peroxidation marker, showed a decreasing trend along the spectrum of risk for BD-I, while there was no difference in the late stage lipid peroxidation markers (4-hydroxy-2-nonenal, 8-isoprostane), protein carbonyls, and inflammatory markers among groups [90]. …”
Section: Resultsmentioning
confidence: 99%